How Does Economy in News Affects News in Economy? - Anastasia Kazun (Journal of Economic Sociology, 2017)
Economic debates in the media and their impact on the economic and political behavior of people are underexamined if compared with similar studies of political or social issues. This paper is aimed at reviewing how economic news are reflected in the academic literature and exploring connections between media, public opinions, and the economic situations. The paper is based on research articles indexed in international citation bases. The most recent relevant texts are selected based on their citations. A special attention is paid to the negative bias in economic news. The author focuses upon the research of economic debates in the media during the financial crisis of 2008. This case is particularly important, because much of the existing research on this topic is devoted to this economic shock. The author concludes that that people's interest in economic information increases when economic situation is instable. At the same time, the character of people's perceptions can affect the media debates.